2018
DOI: 10.2196/10522
|View full text |Cite
|
Sign up to set email alerts
|

Determining Physiological and Psychological Predictors of Time to Task Failure on a Virtual Reality Sørensen Test in Participants With and Without Recurrent Low Back Pain: Exploratory Study

Abstract: BackgroundSørensen trunk extension endurance test performance predicts the development of low back pain and is a strong discriminator of those with and without low back pain. Performance may greatly depend on psychological factors, such as kinesiophobia, self-efficacy, and motivation. Virtual reality video games have been used in people with low back pain to encourage physical activity that would otherwise be avoided out of fear of pain or harm. Accordingly, we developed a virtual reality video game to assess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…This points to two conclusions: First, BSME holding times are reduced in NSCLBP patients because of some other factor that was not measured in the present study, such as reduced motivation 17 , 44 or different recruitment of muscles beyond back extensors 10 , 45 . Second, it appears unlikely that altered back muscle oxygenation and subsequent accumulation of metabolites is a major source of pain in patients with CNSLBP.…”
Section: Discussionmentioning
confidence: 54%
“…This points to two conclusions: First, BSME holding times are reduced in NSCLBP patients because of some other factor that was not measured in the present study, such as reduced motivation 17 , 44 or different recruitment of muscles beyond back extensors 10 , 45 . Second, it appears unlikely that altered back muscle oxygenation and subsequent accumulation of metabolites is a major source of pain in patients with CNSLBP.…”
Section: Discussionmentioning
confidence: 54%
“…The main findings of each study are summarised in S3 Table . From the results retrieved in individual studies, evidence of neuromuscular adaptations in people with rLBP were found for the following outcome domains: muscle activation amplitude [ 34 , 35 , 37 , 38 , 42 , 44 , 48 , 49 , 56 , 57 , 58 60 , 65 , 67 ] and timing [ 13 , 37 , 51 54 , 65 ], spine kinematics [ 34 , 43 , 47 , 50 , 62 – 64 , 66 ], sensorimotor control [ 61 , 62 ], muscle properties [ 45 , 46 , 58 , 68 ], and neuromuscular performance [ 39 41 , 46 , 47 , 55 , 69 ]. For people with rNP, sensorimotor control and neck muscle performance were assessed in the single study included [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This therefore did not assess grit in relation to a musculoskeletal injury and excluded the paper from the review. Similarly, a virtual reality Sørensen test was assessed in participants with and without recurrent low back pain [ 71 ]. Whilst the Sørensen test is a well-known test of muscle endurance, it is used to predict first time episodes and recurrence of back pain [ 71 ], rather than predict functional performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a virtual reality Sørensen test was assessed in participants with and without recurrent low back pain [ 71 ]. Whilst the Sørensen test is a well-known test of muscle endurance, it is used to predict first time episodes and recurrence of back pain [ 71 ], rather than predict functional performance. Five further studies outwardly fit the brief of the scoping review, however upon deeper examination were excluded due to inclusion of presentations not of a musculoskeletal origin [ 72 ], lack of detail to confirm pain of a musculoskeletal origin [ 73 ], use of an optimism outcome measure to assess resilience [ 74 ], absence of results reflecting the assessment of resilience [ 75 ] or use of assessments which were the combination of cognitive and functional domains [ 76 ].…”
Section: Discussionmentioning
confidence: 99%